Too Much, or Else Too Little: How Exile and Objects Affect Sense of Place and Past in Life-Writing Practice. Issue 4 (2nd October 2017) - Juckes, Daniel
ABSTRACT: This paper will examine the effects of exile in life writing practice. It will consider how things from the past can be used to evoke and revoke what James Wood termed 'homelooseness'. It will draw on examples from my own creative practice, a family memoir written from Australia about people in and from the United Kingdom. The memoir is informed by things plucked from a loose and disordered family archive, which exists across both countries. It is driven by a need to locate my own life within its new context in the Asia-Pacific. In the paper I will use the work of W.G. Sebald and Penelope Lively to illustrate the rootlessness things provoke and resist; I will touch on the melancholy inspired by that feeling. As well as showing the reality of dislocation, things-from-the-past can be useful tools for life writers concerned with the past or engaged with the problem of trying to capture slippery, liminal states of being. The conflation of one place or time with another, as described by George Poulet when critiquing Marcel Proust, can be triggered briefly by objects.